Elementos categoriais do conceito de formação em Fichte e Hegel (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: This article offers some reflections, informed by the work of Fichte and Hegel, concerning the categorical concept of Bildung and its possible role in the empirical diagnosis of a cultural decline. It is my claim that the analysis of the concept of Bildung is best approached in a speculative fashion, with a view to articulating a categorical determination thereof, so as to avoid reducing the incidence of such phenomena of decline to a mere historical contingency. Accordingly, the first part of the paper inquires into the categorical conditions of the possibility of Bildung, which it relates, on the one hand, to Hegel’s notion of “sublation” [Aufhebung] and, on the other, suggests a way of understanding them as part of a pre-empirical critique of the idea of the so-called decline of Bildung. The second and the third parts address the concepts of “limitation” [Schranke] and “ought” [Sollen] in Hegel’s Science of Logic and Fichte’s Foundations of the Science of Knowledge, outlining the reasons why these notions belong, qua essential categorical moments, to a proper conception of Bildung. In conclusion, the paper is intended to vindicate the idea of philosophy as the analysis of categorical conceptual structures (e.g. the notion of Bildung), as a way of resisting the tendency to turn the problems of socio-historical value, like Bildung, into a mere matter of politics.